2016
DOI: 10.1007/s10620-016-4145-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Mediates β-Catenin-Driven Downregulation of Claudin-3 and Barrier Dysfunction in Caco2 Cells

Abstract: Background IL-1β is a cytokine involved in mediating epithelial barrier dysfunction in the gut. It is known that IL-1β mediates activation of non-muscle myosin light chain kinase in epithelial cells, but the precise mechanism by which epithelial barrier dysfunction is induced by IL-1β is not understood. Methods and Results Using a Caco2 cell model, we show that the expression of the tight junction protein, claudin-3, is transcriptionally downregulated by IL-1β treatment. In addition, after assessing protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…Garcia-Hernandez et al (47), found that claudin-3 was expressed at lower levels in inflammatory bowel disease. Haines et al (19), found that the protein expression levels of claudin-3 were positively correlated with intestinal epithelial tightness. In the present study, immunohistochemistry, western blotting and RT-qPCR were used to analyse the expression profile of claudin-3 in intestinal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia-Hernandez et al (47), found that claudin-3 was expressed at lower levels in inflammatory bowel disease. Haines et al (19), found that the protein expression levels of claudin-3 were positively correlated with intestinal epithelial tightness. In the present study, immunohistochemistry, western blotting and RT-qPCR were used to analyse the expression profile of claudin-3 in intestinal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still no evidence showing the mechanism of action by which emodin protects the intestinal epithelial barrier integrity during sepsis. Since the integrity of the intestinal epithelial barrier is predominantly maintained by intestinal epithelial TJs, the mechanism by which the intestinal epithelial barrier can be improved has been a focus of research (19). Various TJ proteins are expressed differently in intestinal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Published data have shown a number of factors that are associated with the Tj abnormality-associated epithelial barrier dysfunction. Exposure to proinflammatory cytokine, such as IL-1β, can inhibit the expression of claudin-3 in intestinal epithelial cells [ 26 ]. Our data have added novel evidence to this point by showing that VitD deficiency is one of the causative factors of epithelial barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggest that induction of different miRs can be responsible for the decreased expression of intestinal epithelial claudins during mucosal inflammation. Specifically, miR-29 suppresses claudin-1 level [78], miR-93 inhibits claudin-3 [71], and miR-223 downregulates claudin-8 expression [73]. Of note, claudins are not the only targets for different miRs at epithelial junctions, since this mechanism was also implicated in the expressional regulation of occludin and ZO-1 [79, 80].…”
Section: Regulation Of Aj and Tj Protein Expression In Inflamed Inmentioning
confidence: 99%